2014
DOI: 10.1116/11.20130902
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Vapor Deposited PVDF/TiO2 Nanoparticle Films by XPS

Abstract: In this investigation, thermal vapor deposition was used to synthesize films of polyvinylidene fluoride (PVDF) containing nanoparticles of the ceramic titanium dioxide (TiO2). This ferroelectric polymer has shown promise as a capacitor dielectric material with possible enhanced electrical properties when combined with ceramic nanoparticles. The films were synthesized starting from a mixture of PVDF and TiO2 (rutile phase) dissolved in dimethylformamide (DMF) solvent. The PVDF-TiO2 mixture was vapor deposited o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…K. Prabakaran et al, reported PVDF/ HFP/ TiO 2 nanocomposite with two fold enhancement in dielectric constant upon incorporation of TiO 2 NPs [51]. In another study conducted by J. Iwagoshi et al, it is demonstrated that incorporation of rutile TiO 2 NPs into PVDF host shown promising results for their use as capacitor due to enhancement in electrical properties of the nanocomposite [66]. W. L. Ong et al focused on the development of a hybrid organic-inorganic TiO 2 nanocomposite, which were used as the volatile organic compound (VOC) sensing and photocatalytic degradation with production of hydrogen gas.…”
Section: Electronicsmentioning
confidence: 99%
“…K. Prabakaran et al, reported PVDF/ HFP/ TiO 2 nanocomposite with two fold enhancement in dielectric constant upon incorporation of TiO 2 NPs [51]. In another study conducted by J. Iwagoshi et al, it is demonstrated that incorporation of rutile TiO 2 NPs into PVDF host shown promising results for their use as capacitor due to enhancement in electrical properties of the nanocomposite [66]. W. L. Ong et al focused on the development of a hybrid organic-inorganic TiO 2 nanocomposite, which were used as the volatile organic compound (VOC) sensing and photocatalytic degradation with production of hydrogen gas.…”
Section: Electronicsmentioning
confidence: 99%
“…Gas phase method [15], sol-gel method [16], and microemulsion flame spraying [17] are all common methods for the fabrication of nano-powders with the dimension of 10-100 nm. Besides, some modified methods are also carried out.…”
Section: Introductionmentioning
confidence: 99%